Long-Term Outcomes of Robotic-Assisted Laparoscopic Sacrocolpopexy Using Lightweight Y-Mesh. Issue 3 (March 2020) - Culligan, Patrick J.; Lewis, Christa; Priestley, Jennifer; Mushonga, Nyarai
Abstract : Objective: The objective of this study was to describe anatomic and symptomatic outcomes at 5 years or longer after robotic-assisted laparoscopic sacrocolpopexy using very lightweight polypropylene Y-mesh. Methods: A prospective analysis of consecutive patients who underwent surgery at a single center between 2007 and 2011 was performed. Patients consented to objective and subjective assessment at 5 years or longer postoperatively. Surgical success was defined as meeting all of the following: (1) no retreatment for pelvic organ prolapse (POP) since surgery, (2) no prolapse beyond the introitus, (3) no apical descent below −5, and (4) no prolapse symptoms reported. Secondary outcome measures included Sandvik Incontinence Severity Index, the PFDI-20, the PFIQ-7, the PISQ-12, and the SSQ-8), rates of dyspareunia, mesh complications, and subjects' need for any surgical or nonsurgical prolapse treatment since their index surgery. Results: Eighty percent of the potential study group (253/316) presented for examination and subjective assessment at 5 years or longer after their index surgeries. The surgical success rate was 226 (89.3%) of 253 with no apical failures. Only 4.4% (11/253) of the group met both objective and subjective failure criteria. Sixteen patients were classified as surgical failure owing to subjective criteria alone despite having no significant objective prolapse on examination. Ten patients (4%) elected to undergo subsequent POP repair. These operations consisted of 5 native tissue anterior repairs and 5 native tissue posterior repairs. In addition, 1 patient elected to use a pessary for recurrent anterior POP. The remaining 16 patients who experienced surgical failure elected no further prolapse treatment. Conclusions: Robotic-assisted laparoscopic sacrocolpopexy using very lightweight mesh provided excellent long-term results with no mesh-related complications. Abstract : Robotic sacrocolpopexy using very lightweight Y-mesh provided excellent long-term results with minimal to no mesh-related complications.